2008
DOI: 10.1016/j.ijrobp.2007.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment Sequelae After External Beam Irradiation With or Without Hormonal Manipulation for Adenocarcinoma of the Prostate: Analysis of Radiation Therapy Oncology Group Studies 85-31, 86-10, and 92-02

Abstract: Purpose-Late gastrointestinal and genitourinary morbidity from external beam irradiation used to treat adenocarcinoma of the prostate continue to be a concern of physicians, and patients alike. Additionally for high risk/locally advanced patients the appropriate use of hormonal manipulation in addition to radiation therapy (RT) may increase toxicity. We analyzed three large RTOG studies 85-31, 86-10, and 92-02 to try to address the aforementioned issues.Methods-2,922 patients were accrued with a median follow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 8 publications
2
40
0
Order By: Relevance
“…26 The use of ADT in combination with radiotherapy has been reported to reduce radiotherapy-associated GU and GI toxicity. 28 All patients in the present study underwent ADT, and their therapeutic outcomes were equivalent to or better than that those achieved by administering high-dose (!80 Gy) radiotherapy, which suggests that the combined use of ADT and IMRT might contribute to improved therapeutic outcomes in prostate cancer. Furthermore, our patients showed few serious adverse effects.…”
Section: Discussionmentioning
confidence: 60%
“…26 The use of ADT in combination with radiotherapy has been reported to reduce radiotherapy-associated GU and GI toxicity. 28 All patients in the present study underwent ADT, and their therapeutic outcomes were equivalent to or better than that those achieved by administering high-dose (!80 Gy) radiotherapy, which suggests that the combined use of ADT and IMRT might contribute to improved therapeutic outcomes in prostate cancer. Furthermore, our patients showed few serious adverse effects.…”
Section: Discussionmentioning
confidence: 60%
“…Whether androgen suppression is correlated with increased toxicity is a controversial issue in the literature. 35,36 However, we cannot exclude the possibility that prostate volume reduction after ADT likely yielded the low incidence of acute bladder and rectal toxicity in the WP group. Second, there was a short follow-up period.…”
Section: Discussionmentioning
confidence: 95%
“…A recently published update of the same study demonstrated statistically significant differences in toxicity between the four arms with the neoadjuvant hormone therapy and whole pelvis RT group having the highest rate of late GI toxicity (11). On the other had, a pooled analysis of the RTOG studies 85-31, 86-10 and 92-02 suggested a protective role for AD in terms of GI and GU toxicity (10). It unclear as to whether these conflicting results is related to categorization of toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have suggested that the addition of AD increases the risk of GI and GU toxicity while others have not (7,(9)(10)(11). At Fox Chase Cancer Center, our experience is that the addition of long-term AD (LTAD) significantly increases grade 2 and higher GI and GU toxicity with in patients treated with 3DCRT for locally advanced prostate cancer (9).…”
Section: Introductionmentioning
confidence: 99%